The Legal Certainty Regarding The Division of Movable Property in Marriages Between People of Different Religions, According to The Civil Code - Bayu Yulistio Hidayat; Tahega Alfath Primananda; Heru Kuswanto (Universitas Merdeka Madiun, 2026)
Introduction to the Problem: The problem arises from court rulings that disregard the rights of the husband and grant all of the marital property to the heir’s full siblings. This could potentially conflict with Article 852 of the Civil Code and the final draft of the regulations. Purpose/Study Objectives: To analyze the legal certainty regarding the division of inheritance from marital property in cases of marriages between people of different religions, as stipulated in the Civil Code (KUHPerdata), particularly in situations where there are no children and the husband serves as the heir. Design/Methodology/Approach: This study employs a normative legal approach, using both legislative and case-based analysis. The analysis is based on the Supreme Court’s ruling No. 1120 PK/Pdt/2025. Findings: The research findings show that, as a matter of principle, the husband is considered the first in line to inherit property. He also retains the right to his wife’s dowry, even in the absence of any children. Decisions that ignore these rights reflect a disconnect between legal norms and actual judicial practice, thereby creating legal uncertainty. Therefore, it is necessary for judges to apply the provisions of the Civil Code consistently, in order to ensure legal certainty, fairness, and protection of all parties involved in inheritance matters.